Vocational identity development among unaccompanied refugee minors. (September 2017) - Oppedal, Brit; Guribye, Eugene; Kroger, Jane
Abstract: This study examined educational aspirations and vocational identity formation among unaccompanied refugees in Norway. In Phase 1 we employed questionnaire data from 918 unaccompanied refugees to investigate the effects of demographic information, pre-migration trauma, mental health and acculturation-related factors on their educational aspirations. In Phase 2, data from Identity Status Interviews (ISI) with 29 participants was analyzed to obtain information about vocational identity status distribution and to examine core themes and contextual factors underlying their vocational choices. The findings from Phase 1 showed that none of the theoretically and empirically based included variables had a significant effect on their aspirations. Moreover, the overall regression model was non-significant. We discussed these findings in relation to the strong motivation among unaccompanied minors to create better lives for themselves than they could have in the countries they fled from, irrespective of their traumatic experiences and mental health problems. In Phase 2 the most important themes emerging from the ISIs revolved around age, time, and economics. The remedial education to bridge the pre-flight gap in formal education meant that the unaccompanied refugee youth entered upper secondary school at substantially older ages than their classmates. Their older ages then led them to prioritize economic considerations in making vocational choices, since the support from the Child Welfare Services is discontinued when they reach the age of majority. Consequently, most of them chose short vocational paths toward earning a living, rather than complex roads that led to the realization of their own long-term aspirations. This may have limited the social mobility of unaccompanied refugees.